GUIDELINES FOR IMPROVING THE ACHIEVEMENT OF SUSTAINABLE OTOP INNO-LIFE TOURISM COMMUNITY ENTERPRISES: EVIDENCE FROM THE LOWER NORTHEASTERN REGION OF THAILAND - SUTHIVORAPONGSRI, Saranya; ANGSUKANCHANAKUL, Jetsarit; Maneechai, Samniang (Asian Administration and Management Review, 2023)
The objectives of this research article are to identify factors that influence the achievement of sustainable OTOP inno-life tourism community enterprises and to offer the approaches in improving the achievement of sustainable OTOP inno-life tourism community enterprises. The quantitative data were collected from 300 members of community enterprises in the lower northeastern region of Thailand. In addition, 16 in-depth interviews were conducted with the group leaders of community enterprises and the district development officers. The results indicate that the achievement of sustainable OTOP inno-life tourism community enterprises in the mentioned area are at a high level. The factors influencing the achievement of sustainable OTOP inno-life tourism community enterprises include development of tourism communities, development of tourist attractions, development of products and services, and marketing promotion. Therefore, in improving the achievement of sustainable OTOP inno-life tourism community enterprises, all four factors need to be interconnected. The main goal is to create a community market to attract visitors, which, in turn, generates employment, increases income, and strengthens the grassroots economy. Nevertheless, entrepreneurs must receive vocational training to produce quality products and services.